Skepticism and School Desegregation - Bradley W. Joondeph (Washington University Law Quarterly, 1998)
While I still believe strongly that integration is a goal worth pursuing, both for intrinsic and instrumental reasons, I question the wisdom of continuing to pursue desegregation through the federal courts into the indefinite future. My skepticism is based on three principal conclusions. First, the objectives attainable through the continuation of court-ordered desegregation are extraordinarily limited compared to the enormity of the problem of racial disparities in public education. Second, over the long term, there are reasons to think that initiatives in the political process will produce more meaningful gains for disadvantaged students than will ongoing litigation. Finally, extricating school desegregation from the courts might have the salutary effect of shifting attention from the narrow objective of compensating the victims of past de jure segregation to the more pertinent goal of eliminating systemic racial disadvantage in American public education.
Keywords: School integration; Law schools; Race